2010
DOI: 10.1590/s1516-35982010000600025
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de ácidos graxos e composição química do músculo longissimus dorsi de cordeiros alimentados com dietas contendo polpa cítrica

Abstract: trans-11). Não houve alteração na concentração total de ácidos graxos saturados, monoinsaturados e poliinsaturados.Entretanto, a quantidade de gordura intramuscular do longissimus dorsi diminuiu com o aumento de polpa cítrica na ração, sem alterar os teores de umidade, proteína e cinzas. A substituição do milho por polpa cítrica na ração modifica a quantidade e o perfil de lipídios do músculo longissimus dorsi de cordeiros.Palavras-chave: co-produtos, ácido linoleico conjugado, ovinos, pectina, Santa Inês Fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
4
0
3
Order By: Relevance
“…This manipulation may be carried out by using different vegetable-origin ingredients, as occurred in the studies made by Rodrigues et al (2010) and Karami et al (2013), and vegetable oils, such as linseed, as suggested by Zhang et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…This manipulation may be carried out by using different vegetable-origin ingredients, as occurred in the studies made by Rodrigues et al (2010) and Karami et al (2013), and vegetable oils, such as linseed, as suggested by Zhang et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the nutraceutical parameters that are strongly correlated with the risk of cardiovascular diseases and obesity in humans [62], no significant difference was observed with different levels of palm silage or water availability, however, it was observed that AI and TI presented averages of 0.35 and 0.91, respectively, which are considered ideal because they are below the average recommended by Ulbricht and Southgate [29] for lamb meat that is from 1.00 for AI and from 1.33 to 1.58 for TI. The lower these values in the lipid fraction of the product, the higher the prevention of the early stages of cardiovascular diseases [63].…”
Section: Plos Onementioning
confidence: 99%
“…Arruda et al [63] studied the relationships or ratios among fatty acids, with the objective to verify and identify the risk factors of food in relation to the increase in blood cholesterol levels in humans. Since the intermittent water supply of up to 48 h did not alter any fatty acids, their ratios and indices were also not influenced, indicating that no parameters of the lipid profile of the lamb meat were changed.…”
Section: Plos Onementioning
confidence: 99%
“…Fazendo substituição parcial ou total do milho pela PC na ração de cordeiros em confinamento, avaliando o perfil de ácidos graxos e composição química do músculo longissimus dorsi, Rodrigues et al (2010), observaram que houve aumento linear na concentração de acido linoléico quando houve substituição total do milho pela PC, esta elevação torna-se desejável por este ácido graxo ser o precursor de ácido graxos poliinsaturados que estão relacionados a TIGRE, J.S. Uso de polpa cítrica peletizada na alimentação de ruminantes, revisão.…”
Section: Uso Da Polpa Cítrica Na Alimentação De Ruminantesunclassified